Literasi Digital Marketing dan Inovasi Produk Bagi Nelayan Teripang Pulau Soop: Pengabdian - Edward Clan; Dwi Indah Widya Yanti; Lili Sarce Joy Sapari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This Community Service Program focuses on the economic empowerment of sea cucumber fishermen in Soop Island, Sorong City, Southwest Papuan through digital marketing training and product innovation with improved packaging. Sea cucumber fishermen in Soop Island face challenges such as limited market acces, low digital literacy, and a lack of innovation in processing and packaging, which result in low product value and dependence on middlemen. The program is carried out in five stages : (1) program socialization to the patner community; (2) training on digital marketing and product innovation; (3) application of appropriate technology through the use of digital platforms and product packaging design; (4) mentoring and evaluation of implementation; (5) formulation of program sustainability strategies. Preliminary result show an improvement in fishermen’s skills in using as social media and online marketplace as tools for promotion and sales. Furtjermore, product packaging innovation has added value to sea cucumber product, making them more marketable to urban cunsumers. The impact of this program includes increased digital literacy, marketing skill, among fishermen, which are ecpected to contribute to income growth and the sustainability of coastal community businesses